Iodine value in pregravidal period of a woman's life - R M Yesayan; A V Sekinaeva (IP Berlin A.V., 2014)
Iodine is an essential trace element, which is essential for the formation and development of a complete organism. Attempts to eliminate iodine deficiency are reduced to mass prevention by iodination of certain foods, but it is not possible to prevent iodine deficiency in groups with an increased need for this groups. This demonstrates the need for drug use potassium iodide into the population groups for which iodine deficiency is the most dangerous - for pregnant, lactating women and children. Iodine deficiency can cause mental retardation, which creates health and social threat to many countries of the world, therefore the world conducts research on the basis on the dose of potassium iodide to prevent iodine deficiency in different populations.